Cyber Politict: Kajian Terhadap Penggunaan Facebook Sebagai Aktivitas Politik Di Ruang Cyber - Intihaul Khiyaroh (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
In a broader context, media convergence actually shows not only the rapid development of technology. Convergence changes the relationship between technology, industry, markets, lifestyles and audiences. In short, convergence changes the patterns of relations of production and consumption, whose use has serious impacts on various fields such as economics, politics, education and culture. In developed countries such as America there is a downward trend in print media customers and rising internet customers. It is even predicted that in the coming decades in the country people will leave traditional mass media and switch to convergent media. If such trends spread to various countries, it is not impossible that one day the role of the online press will replace the role of the traditional press. There are two big points in cyberpolitic: First, cyberpolitic moves political activity from the world off to the world on. Second, politics really only exists in the cyber world and does not exist in the real world. If in China people are not allowed to use Facebook as social media. Facebook is blocked and cannot be opened. Apparently this is used for military and political purposes.